2019
DOI: 10.1016/j.abrep.2019.100209
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive mechanism of intimate interpersonal relationships and loneliness in internet-addicts: An ERP study

Abstract: Interpersonal relationship and loneliness are important factors affecting internet addictive behavior of individuals. In the present study, we investigated intimate interpersonal relationships and loneliness in internet-addicts. We recorded event-related potentials (ERPs) of 32 internet addicts and 32 non internet-addicts. Participants viewed intimate-/conflict-relationship, happy/lonely, and neutral images. Results concerning attention probes showed that the accuracy rate of attention probes of internet-addic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 50 publications
0
13
0
5
Order By: Relevance
“…Wang and Griskova-Bulanova (2018) involved a non-clinical sample of 22 adults (54.5% males). Senormanci et al (2014) conducted a study on a clinical sample of 40 young adult Turkish males, and the study by Hou et al (2019) recruited 32 Internet addicted and 32 non-addicted adult Chinese males. The South Korean adolescent clinical sample recruited by Ryu et al (2019) consisted of 103 children and adolescents (aged 7-18) with excessive Internet use (70.9% males) and their caregivers (92.4% females).…”
Section: Risk Factors: Samples and Prevalence Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang and Griskova-Bulanova (2018) involved a non-clinical sample of 22 adults (54.5% males). Senormanci et al (2014) conducted a study on a clinical sample of 40 young adult Turkish males, and the study by Hou et al (2019) recruited 32 Internet addicted and 32 non-addicted adult Chinese males. The South Korean adolescent clinical sample recruited by Ryu et al (2019) consisted of 103 children and adolescents (aged 7-18) with excessive Internet use (70.9% males) and their caregivers (92.4% females).…”
Section: Risk Factors: Samples and Prevalence Ratesmentioning
confidence: 99%
“…Depression, anxiety and impulsivity had partial to full mediating effects on the ability to aggression to predict GIA, but no effect on the ability of GIA to predict aggression (Lim et al, 2015). In an exploration of Event-Related Potential (ERP) patterns, when subjects were presented photos of intimacy, conflict, happiness and loneliness, researchers found social cognitive function and attention function was impaired in the IA group (Hou et al, 2019). Tateno et al (2019) found subjects at high risk for hikikomori, severe social withdrawal, had longer Internet usage time and higher scores on IAT.…”
Section: Risk Factors Associated With Giamentioning
confidence: 99%
“…Logo, há difi culdade para a diferenciação do seu uso patológico ao considerado normal, por ser um serviço de fácil acesso pelas diferentes classes e grupos sociais. Sua utilização vai de acordo com as diferentes motivações e o desejo do sujeito em procurar por algo que atenda às suas expectativas 19,20,21 .…”
Section: Perspectivas Comportamentaisunclassified
“…A dependência da internet pode desencadear sinais e sintomas de ansiedade: dispneia, dor ou aperto no peito, elevação da frequência cardíaca, cansaço e fraqueza 10,11,12,28,30,32 . E sintomas depressivos, ou seja, irritabilidade/raiva, fadiga, culpa, inutilidade, tristeza, pessimismo e desesperança 21,29,30,31,32,33 . Essa sintomatologia pode afetar qualquer idade, porém, nos adolescentes, é bastante frequente, devido ao processo de formação da autoimagem e autoestima 34 .…”
Section: Infl Uências Psíquicasunclassified
See 1 more Smart Citation